Human values and service quality in commercial banks of Malaysia: Mediating role of behavioural outcome / Zahra Kamiab - Zahra, Kamiab (2017)
There has been a significant diversity of opinion concerning the critical and effective role of values in human behaviour outcomes on organisation’s service quality. The Malaysian government has made tremendous structural changes to commercial banks that have led to mergers to ensure the banks could survive pressures of time. The banks always attempt to ensure their staff are equipped with the required knowledge and meets the expectation of the customers. For Malaysia, commercial banking represents about 70 percent of the financial system’s total assets. They are regarded the main pillars of a financial system, as they are the largest and the most salient contributor of funds. Also, the study of values has been distinct by various methodological styles and conceptual framework used. In this study, the researcher examined the relationships between human values, the service quality of Malaysian commercial banks, and the mediating effects of employees’ behavioural outcome, including organisational citizenship behaviours (OCBs), employees’ abilities and employees’ motivation. The four higher dimensions of human values studied include self-enhancement, openness to change, self-transcendence, and conservation. Data were collected by the use of a questionnaire on all branches of two commercial banks of Malaysia (65 branches of bank B1 and 52 branches of bank B2) totalling 117 branches all located in Kuala Lumpur. From each branch, three staff and five customers served as the source of the primary data. Thus, a total of 351 personnel and 585 customers participated in this study. To test the mediation model and to examine if the hypothesised model fits the data, Structural Equation Modelling (SEM) analysis was used. PLS software was used to analyse the measurement model and structural model for the direct and indirect relationships between human values and service quality; including employees’ behaviour outcome variables as mediator variables. The results show that employees’ ability mediated the relationship between conservation, self-enhancement and openness to change value and service quality. It was further realised that OCBs mediates the relationship between conservation value and service quality. So motivation of employees only mediates the relationship of self-enhancement value and service quality. Further, the result shows self-transcendence value does not have any effect on service quality in direct and also indirect paths. Overall, this study provides a more comprehensive understanding of the important role of human values in increasing service quality in the banks. The findings of the current study provide insights into the role of human values, OCBs, employees’ ability, and employees’ motivation in service quality. Hence, organisations need to focus on recognising and understanding their employees’ values, thereby, enhancing especially employees’ ability to achieving higher service quality. Therefore, under such good attention, a benign cycle will be formed which promotes the employees’ behaviour outcome variables of employees to improve service quality that comes from personal values. In terms of managerial implications, managers must allocate more attention on their employee’s ability, OCBs and motivation through their values that lead to improved service quality. Based on research findings most of the employee values influence service quality through their ability. This study recommends the need to check for best strategies and select the types of services that should be provided in attending to employee’s behaviour through their personal values.